2017
DOI: 10.18632/oncotarget.21751
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy use and survival in stage II nasopharyngeal carcinoma

Abstract: Although common, the use of chemotherapy for stage II nasopharyngeal carcinoma (NPC) is controversial due to its undefined clinical benefits. We therefore conducted a retrospective cohort study to investigate whether chemotherapy confers survival gains to stage II NPC patients. A total of 251 stage II (2010 UICC/AJCC staging system) NPC patients treated between January 2007 and December 2014 were retrospectively analyzed. Patients were matched using the propensity-score matching method. The primary endpoint wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Luo et al19 reported that the 3-year OS rate was worse in T2N1 patients than in T1N1 and T2N0 patients (74.5 vs 100.0%, respectively; p =0.01). However, other studies have found that the survival rates were not different between the T1N1, T2N0, and T2N1 subgroups 3,2123. The prognosis of the three subgroups remains controversial.…”
Section: Discussionmentioning
confidence: 94%
“…Luo et al19 reported that the 3-year OS rate was worse in T2N1 patients than in T1N1 and T2N0 patients (74.5 vs 100.0%, respectively; p =0.01). However, other studies have found that the survival rates were not different between the T1N1, T2N0, and T2N1 subgroups 3,2123. The prognosis of the three subgroups remains controversial.…”
Section: Discussionmentioning
confidence: 94%
“…The characteristics of the patients included in the 14 eligible studies 17‐30 are shown in Table 1. A total of 4086 participants were involved in this meta‐analysis, of whom 2014 received CCRT with additional chemotherapy and 2072 received CCRT alone.…”
Section: Resultsmentioning
confidence: 99%
“…Ten studies 17‐20,23‐25,27,28,30 investigated IC + CCRT, which included 1431 participants. Moreover, four trials 21,22,26,29 explored CCRT + AC in 583 patients. Eleven studies 18‐20,22‐29 involved 1:1 PSM analysis, Two studies 21,30 involved 1:2 PSM analysis, and 2:1 PSM analysis was conducted in only one study 17 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, some researchers have attempted to assess the efficacy of AC in patients with stage II NPC. Pan et al 26 reviewed 251 stage II (according to the 2010 UICC/AJCC staging system) NPC patients treated with IMRT using the PS matching method. The Kaplan-Meier survival curves showed no significant difference in OS (P=0.200), LRFS (P=0.204), or DMFS (P=0.064) in patients treated with RT alone, CCRT, or CCRT + AC.…”
Section: Adjuvant or Induction Chemotherapy Combined With Imrt For Stmentioning
confidence: 99%